Asuhan Keperawatan Gerontik Pada Pasien Dengan Gout Arthritis Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Annisa Aulia; Sandra Dewi; Hasmita .; Armaita . (CV. ITTC INDONESIA, 2026)
Based on data from the World Health Organization (WHO), the prevalence of gout arthritis at the global level increased in 2023, where the number of sufferers was around 44,000,000 people with a prevalence of 0.56%. Gout arthritis is a disease caused by a purine metabolism disorder that causes the accumulation of uric acid crystals in the joints. This condition is influenced by age, purine consumption, with symptoms such as pain, swelling, stiffness. If left untreated, it can cause joint damage and kidney disorders. The purpose of this study is for the author to be able to provide nursing care to elderly people with gout arthritis. The research method used was a case study for 6 days through interviews, observations, and checking uric acid from February 26 to March 3, 2026. The results of the study obtained 3 nursing diagnoses, namely: chronic pain, impaired physical mobility, ineffective health management. Where the interventions described are pain management, mobilization support, decision-making support and implementation carried out according to the prepared plan. After 5 days of implementation, the results obtained were reduced pain, decreased uric acid levels, increased mobility, and improved health management. The evaluation on the fourth day showed that the diagnosis of ineffective health management was resolved, and the diagnosis of chronic pain and mobility impairment was not resolved, so the caregiver continued. Educating the client to take medication regularly according to the prescribed dosage, maintaining a healthy diet, for example, reducing consumption of coconut milk and green vegetables, and educating the caregiver by reminding the client to take medication regularly, inviting the client to participate in activities held by the nursing home, such as exercise, health education, and arts.